2020
DOI: 10.21438/rbgas(2020)071709
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade genética em genótipos de Capsicum annuum L. (Solanaceae) promissores para uso ornamental

Abstract: O mercado brasileiro de pimentas ornamentais tem apresentado expressivo crescimento, exigindo o conhecimento de características relacionadas a essa finalidade. O presente trabalho teve como objetivo analisar a diversidade genética em pimentas Capsicum annuum L. (Solanaceae) utilizando-se de características qualitativas e quantitativas para a seleção de genótipos promissores para uso ornamental. O experimento foi conduzido em casa de vegetação em delineamento inteiramente casualizado com 11 genótipos e três rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Rêgo et al (2012) evaluated pepper plants with ornamental potential and found means of 50 days to flowering and 91 days to fruiting. Silva et al (2020) evaluated promising materials for ornamental use and found 85 days to flowering and 103 days to fruiting for the earliest genotype. These are similar results to those found in the present study.…”
Section: Qualitative Descriptorsmentioning
confidence: 99%
“…Rêgo et al (2012) evaluated pepper plants with ornamental potential and found means of 50 days to flowering and 91 days to fruiting. Silva et al (2020) evaluated promising materials for ornamental use and found 85 days to flowering and 103 days to fruiting for the earliest genotype. These are similar results to those found in the present study.…”
Section: Qualitative Descriptorsmentioning
confidence: 99%
“…Very tall plants with a wider crown do not adapt well to the pot, resulting mainly in the plants tipping over. Very small plants end up not standing out on the pot, directly compromising the aesthetics and visual balance (Silva et al, 2020). The evaluation of these parameters is traditionally carried out when the rst fruits ripen, using a ruler and caliper (IPGRI et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Nos últimos tempos, a maior parte do mercado de pimentas é integrada ao comércio de produtos alimentícios, incluindo formas in natura e processadas, como molhos, conservas, geleias, pápricas, corantes e aromatizantes (SILVA et al, 2020;VÁZQUEZ-ESPINOSA et al, 2020). Além disso, por meio do cultivo, é possível gerar outros produtos para atender várias demandas do mercado, como plantas ornamentais, repelentes de insetos, sprays de autodefesa e compostos benéficos para a saúde (FERRAZ et al, 2016;VÁZQUEZ-ESPINOSA et al, 2020).…”
Section: áRea Do Conhecimento: Ciências Biológicas -Genética Introduçãounclassified